Determinants of internationalisation: Do they differ among sectors and business functions? Evidence from firm-level data - Spyros Arvanitis; Heinz Hollenstein; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2013)
The relevance of services FDI strongly increased over the last two decades. As goods and services differ with respect to important characteristics, one may expect that the determinants of internationalisation are not identical in manufacturing and the service sector. However, there is practically no firm-level research contrasting the two sectors in this respect. In order to fill this gap, we seek to identify for manufacturing and services, firstly, the determinants of a firm's propensity to go international (exports and/or foreign direct investment) and, secondly, the factors determining the complexity of a firm's direct foreign activities in terms of business functions. We find that an OLI-based model can be used to explain not only the propensity to go intenational but also differences between two specific forms of direct foreign investment for both the manufacturing and the service sector.
Keywords: F23; 330; Manufacturing vs. services internationalisation; offshoring vs. exports; internationalisation of business functions; multinational companies; international business strategy